A Decision Support System to Determine the Familiy’s Economic Status for Certificate of The Low-Income Household Using MAUT Method - Muhammad Yahya; Jumadi Mabe Parenreng; Fathahillah Fathahillah; M. Syahid Nur Wahid; Muhammad Fajar B; Abdul Wahid (P3M Politeknik Negeri Bengkalis, 2022)
The problem of unemployment and poverty is a significant issue that the government have yet to address completely. The number of working-age people continues to rise, yet there are insufficient employment openings to meet demand. The government then provided extensive aid to the community. The Village Information System, part of the digitization system in Laguruda Village, Takalar Regency, comprises an integrated intelligent system that can forecast the eligibility of people who come to apply for a certificate of incapacity so that they are no longer inappropriate targets. The method employed is the Multi-Attribute Utility Theory (MAUT), based on 14 criteria set forth by the Ministry of Social Affairs. The results of a 49-person sample of household heads who identified themselves as poor and in need of assistance from the Ministry of Social Affairs revealed that 57.14% were in the mediocre category, 36.73% were in the rich category, 4.08% were in the poor category, and 2.04% were in the very poor category. This information demonstrates the system's ability to filter requests for poverty certifications. On the other hand, village officials were assisted in determining the right conditions for residents to be eligible for a poverty certificate